2019
DOI: 10.1136/bmjopen-2019-029714
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of hypertension among persons aged 15–49 in India: a cross-sectional study

Abstract: ObjectivesThis is the first attempt to provide estimates on the prevalence of hypertension at the national, state and district level, a prerequisite for designing effective interventions. Besides, the study aims to identify the risk factors of hypertension.DesignWe analysed cross-sectional survey data from the fourth round (2015–2016) of National Family Health Survey (NFHS). NFHS was conducted between January 2015 and December 2016, gathering information on a range of indicators including blood pressure. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
59
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 19 publications
15
59
3
Order By: Relevance
“…14 Similar to the findings of Sumitra G et al who found that overweight or obese persons were significantly more likely to suffer from hypertension (OR=2.02, p<0.001 and OR=3.22, p<0.001, respectively). 15 In this study family history was significantly associated with hypertension. Similar results were found by Radhakrishnan et al among the tribal population of Tamil Nadu Naresh et al also found positive family history was strongly associated with hypertension in rural population.…”
Section: Discussionsupporting
confidence: 47%
“…14 Similar to the findings of Sumitra G et al who found that overweight or obese persons were significantly more likely to suffer from hypertension (OR=2.02, p<0.001 and OR=3.22, p<0.001, respectively). 15 In this study family history was significantly associated with hypertension. Similar results were found by Radhakrishnan et al among the tribal population of Tamil Nadu Naresh et al also found positive family history was strongly associated with hypertension in rural population.…”
Section: Discussionsupporting
confidence: 47%
“…This mixed-method study explored the knowledge and experiences of patients impacting health-seeking behavior for hypertension, in rural India. In a recent study by Ghosh and Kumar,[ 10 ] the prevalence of hypertension was found to be higher in urban areas, with small rural-urban differences thereby implying the rapid spread of the epidemic of hypertension even in the rural population. This increasing prevalence of hypertension in the rural population may present serious implications as the public health system through primary health centers in rural areas is still focused on infectious diseases and reproductive and child health making people rely on the private sector for the management of hypertension and its associated complications, thus adding substantially to their financial strain.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a change in the categorisation of blood pressure from The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC7) to the recent guidelines followed by ACA/AHA (26) . Most of the earlier reports were based on the JNC6 or JN7 classification (12)(13)(14)(15)(16)18,20,24) . In the recent guidelines the SBP and diastolic BP has been fixed in the normal and elevated BP group to <120 mmHg and < 80mm Hg respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension across the World Health Organization (WHO) region was highest in Africa at 46% and lowest in America at 35% for both sexes (10) . In India the prevalence of the disease varies from 9.3% to 47.9% in different sets of population of the country (11)(12)(13)(14)(15) . The prevalence of elevated BP in urban dwellers varied between 11.5% -31.5% and that in rural population from 10.6 % -33.8% (12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation